Control interno del proceso contable en el Gobierno Autónomo Descentralizado Municipal del Cantón de Baba, periodo 2021. - Onofre Valero, Génesis Clariza (2022)
The present study focuses on examining the internal control of the accounting process in the Decentralized Autonomous Government of the Baba Canton for the period 2021, in order to reveal the key points and the shortcomings that still exist. The data obtained from the survey was carried out in the finance department, in the accounting area where the capital estimate was planned to carry out all the activities of the GAD, where the existing deficiencies in the control were discovered. performed activities. The risk factors detected were mainly control risk, with a poor application of the internal control procedures suffered by the internal processes brought to the financial department. It is important that the Decentralized Autonomous Government of the State of Baba find development mechanisms to overcome existing problems and provide a quality and timely works and projects service, ensuring the economic and social development of the people. In this research, my focus is on reviewing and identifying solutions to overcome deficiencies in accounting management, design control documents and identify tools that facilitate the optimization of internal control in the Decentralized Autonomous Government of the State of Baba.